Evaluation of Drying Characteristics of Selected Fishes in Dryers developed by ICAR-CIFT - Fasludeen, N. S.; Murali, S.; Samuel, Manoj P.; Ninan, George; Joshy, C. G. (Fishery Technology, 2018)
ICAR-Central Institute of Fisheries Technology,Cochin, has developed different types of dryers forimproving the quality of dried fishes i.e. Solar traydryer with electrical back up (hybrid), Solar tunneldryer, Electrical dryer and Solar cabinet dryer withelectrical back up (hybrid). Drying characteristicsstudies on selected fishes, mackerel (Rastrelligerkanagurta) (80% moisture content (MC) on wet basis(wb) and glassy perchlet (Ambassis spp.) (77% MCon wb), was conducted using the solar tray dryerwith electrical back up (hybrid) dryer. Thetempeature obtained inside the chamber duringdrying was 65oC. The solar tunnel dryer, electricaldryer and solar cabinet dryer with electrical back up(hybrid) was evaluated with fresh and salted solefish (Cynoglossus semifasciatus) (77% MC). Solartunnel dryer under normal atmospheric conditionsattained 45°C temperature, Electrical dryer wasoperated at 65°C temperature and Solar cabinetdryer with electrical back up (hybrid) attained 70°Ctemperature. Among the CIFT dryers evaluated,electric dryer was found to yield lower moisture dryproduct. Also, fish dried under electrical dryerreceived highest overall acceptability in sensoryevaluation study.